Study of incidental carcinoma of the prostate. Part 1. Pathological analysis related to the clinical features - Fujita, T (Hinyokika kiyo. Acta urologica Japonica, 1991)
To clarify the clinico-pathological characteristics of incidental carcinoma of the prostate, we investigated a total of 590 prostatic tissues which had been operated under the diagnosis of benign prostatic hyperplasia (BPH), including 12 whole prostatic specimens which were obtained by total cystectomy due to bladder cancer. Histological examination and estimation of the tumor volume were carried out by either a 3-mm step-section in 185 prostates obtained by open surgery, or by mounting whole specimens in 405 TUR cases. Incidental cancers were detected in 69 of the 590 patients (12%) with nearly equal numbers of stage A1 and stage A2 diseases. The age and the size of the prostate were significantly greater in the patients with cancer, compared to those without cancer. However, these parameters were not in agreement with each other. Histological analysis revealed that 46 of the 69 (67%) incidental cancers were well differentiated and nearly corresponded to Gleason's sum score of 2-4. In the analysis of the differentiation of the tumor cells and the tumor extension, nearly 80% of the 23 well differentiated cancers were manifest in a single lesion and were smaller than 0.3 cm3, whereas 90% of the 11 moderately or poorly differentiated cancers were diffusely invasive. Six of the 11 cases (55%) were larger than 0.3 cm3. The prognosis of the 16 incidental cancer patients who had survived more than 5 years after the surgery were compared with the controls. The controls were selected among the cases without incidental cancer, and matched for age and the time of operation in a 1 to 2 fashion without knowledge of their prognoses.(ABSTRACT TRUNCATED AT 250 WORDS)